Keanekaragaman dan komposisi kumbang elaterid (Coleoptera: Elateridae) di kawasan hutan hujan tropis Taman Nasional Bukit Duabelas dan Hutan Harapan, Jambi - Kasmiatun Kasmiatun; Rizky Nazarreta; Damayanti Buchori (Jurnal Entomologi Indonesia, 2020)
Jambi province is one of the regions in Indonesia that has tropical rainforests with different landscape characteristics in each region. Tropical rainforests contain the highest biodiversity in the world and as a habitat for various types of flora and fauna, including elaterid beetles. Elaterid beetles have an important role as ecological bioindicators. The aim of this research was to study the diversity and species composition of elaterid beetle in two different landscape types. Insect sampling was carried out in Jambi Province on two tropical rainforest landscape, i.e. Bukit Duabelas National Park (TNBD) and Harapan Rainforest. Elaterid beetles were collected by canopy fogging method in the morning. Each landscape consists of four core plots and each core plot consist of three as subplot, total subplots observed in both landscape were 24 subplots. A total of 2069 individuals of elaterid beetles were collected, belonging to 6 subfamilies, 23 genera, and 59 morphospecies. The abundance of elaterid beetles was higher in Harapan Rainforest, while species richness was higher in TNBD landscape. Species dominant in two landscape consist to subfamily Agrypninae, belonging to genera Adelocera with morphospecies Adelocera sp.01. The result of this research showed that landscape differences influencing the composition and abundance of elaterid beetles, but it does not influence in species richness of elaterid beetles.